O papel do youtuber como incentivador de novos modelos de leitura e produções audiovisuais na escola - Marangoni, Júlio César (2020)
From analysis of changes occurred in the means of communication with the surface of youtubers, some of whom started to exert influence, form opinions and whom have become writers with a big following, popular amongst kids, teenagers and adults, this research has as a general goal to elaborate a proposition to encourage the reading and production of audiovisual texts, an environment in which the non-verbal sign is predominant, from the concept of youtuber and its possible connections with high quality literature understood as a verbal sign. The research’s theme is the audiovisual production made by the youtuber, understood as an environment of language capable of verbal and non-verbal readings and of creative productions. As specific objectives, we list: understanding audiovisual productions as a language (verbal and non-verbal); studying some problems related to education in verbal and non-verbal aspects; characterizing the profile of the youtuber (What does he produce? How does he produce? To whom does he produce?); reflecting upon possible influences of digital content creators, predominantly the youtuber; the transdisciplinarity and propose actions related to readings and creative productions by audiovisual means. Our starting point is the hypothesis that a teacher can use youtubers’ productions as a means of encouragement and production of audiovisual content by the students and that this would be a path to reach high quality literature. The corpus of the research comprises a selection of some videos by youtubers who work with literary content and that relate to our thematic focus, aiming to make the most of that content to expand the concept of literature in educational formation. The methodology used was the semiotic analysis of the above-mentioned videos based on the concepts addressed mainly by Lucia Santaella. Throughout the thesis, within the conceptual thematic approaches pertinent to our argumentation, we seek, opportunely, base ourselves in Paulo Freire, Zygmunt Bauman, Edgar Morin, Henry Jenkins, Gilles Deleuze e Jean-Paul Sartre. In the last chapter we present a proposition of intervention with the encouragement of reading and audiovisual content creation, where we also present the fact that activities such as the one proposed by us are backed by the Base Nacional Comum Curricular (the new Brazilian curricular standards), confirming our initial hypothesis that a teacher can use youtubers’ production as a means of encouragement and production of audiovisual content by the students, creating transdisciplinary projects.